The Impact Of Constitution Court Decision About The Abolition Of RSBI/SBI Program Case Study on ex.SDBI No.26 Argamakmur North Bengkulu Regency - Supriyanti, Yuni Indah (TADBIR : Jurnal Studi Manajemen Pendidikan, 2017)
The need of education which is properly accommodated in Constitution Number 20 of 2003 about national education System on article 50, verse 3 which mandate that Government and/or Local Government hold at least one educational unit on whole educational level to be developed as school at international level. After 8 year implementation, through Constitution Court session on Tuesday, January 8, 2013, issued a policy about abolition of international based school. Constitution Court has accepted the complaint which is submitted by Coalition against Commercialization of Education. In its consideration, Constitution Court considers that international school in governmental school is on the contrary to UUD 1945. The purpose of this research is to know about the impact of Constitution Court decision (The Abolition of RSBI/SBI Program) in schools and public institutions in this case about student guardian. This research is also expected to be able to give contribution for knowledge and science especially to research policy in education. The method of this research is qualitative research and case study. This research is held in SDN 26 Argamakmur which is one of Pioneering International School (RSBI). This research uses some informants; they are teachers and administration staffs of SDN 26 Argamakmur, student guardians, the officials of education and culture department of North Bengkulu regency and the officials of education and culture department of regional offices and also some policy experts in the field of education. This research finds out some facts that Constitution Court decision about the revocation of RSBI in SD BI 26 Argamakmur causes the result of psychology pressure for teachers as the spearhead of policy implementer. Before this decision published, the teachers who teach in this school have their own pride to teach in this school. Physically, RSBI School in Argamakmur has some facilities such as computer laboratory, Language laboratory, and ICT room. These facilities need high maintenance fund. Therefore, regional government still has responsibilities toward the impact of status alteration of this school. The alteration of status from RSBI school to regular school results on various impact for society especially students guardian. For the parents who have sent their children to RSBI School, there is a pride form the parents toward their children because they have basic skills that arenât given in other schools. The skills are active English skill and computer skill. Many parents who have their children study in International Standard Primary School (SD BI) feel disappointed since there wonât be written international standard school in their childrenâs educational certificate. International predicate is considered as a pride for some parents. The steps taken by school have been based on circular letter of education and culture Minister of Indonesia dated January 30, 2013. That circular letter contents RSBI transition policy. Keywords: Impact, Constitution Court decision, RSBI program.